„Nie więcej jak powinność robimy naszą” – czyli o działalności Antoniego Downarowicza podczas pierwszej wojny polskiej - Drzazga, Damian (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
This paper aims to bring Major Antoni Downarowicz and his role during the Polish campaign of 1806/1807, particularly concerning the siege of Gdańsk in 1807, close to the readers. The source basis were the letters written by Downarowicz and army officers who served with him at the time in the so-called Dąbrowski Division.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne